Investigation of Thiol Levels in Young Commercial South African Sauvignon Blanc and Chenin Blanc Wines Using Propiolate Derivatization and GC-MS/MS - Coetzee, C.; Schulze, A.; Mokwena, L.; du Toit, W.J.; Buica, A. (South African Journal of Enology and Viticulture, 2018)
In this work, the ethyl propiolate method for analysing thiols in white wine by GC-MS, originally proposed by Herbst-Johnstone et al.) (2013), has been adapted to GC-MS/MS and has been validated. The method performance has shown improvement in terms of sensitivity (limit of detection, LOD) and of the number of compounds measured. In addition to 3-mercaptohexanol (3MH), 3-mercaptohexyl acetate (3MHA), and 4-mercapto-4-methylpentan-2-one (4MMP), the adapted method can also measure 2-furanmethanethiol (FMT) and makes use of a commercially-available internal standard (IS), 4-methoxy-2-methyl-2-butanethiol (4M2M2B, IS). The proposed method was applied to determine thiol levels in young commercial South African Sauvignon and Chenin Blanc wines. The samples (n=20 for each cultivar) were chosen according to a high frequency of the typical descriptors associated with this class of impact compounds. 3MH was found at 178-904 ng/L and 99-1124 ng/L, and 3MHA at 23-151 ng/L and 5-253 ng/L in Sauvignon and Chenin Blanc respectively. 4MMP was present in Sauvignon Blanc in concentrations up to 21.9 ng/L, but in none of the Chenin Blanc samples.